2016
DOI: 10.1021/acs.jpclett.6b01806
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Internal Fields in a Biased Graphene–Insulator–Semiconductor Structure

Abstract: Measuring and understanding electric fields in multilayered materials at the nanoscale remains a challenging problem impeding the development of novel devices. At this scale, it is far from obvious that materials can be accurately described by their intrinsic bulk properties, and considerations of the interfaces between layered materials become unavoidable for a complete description of the system's electronic properties. Here, a general approach to the direct measurement of nanoscale internal fields is propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…If correct, our findings might suggest that a diode could represent either the electrical double layer at the PEG/Teflon interface or the leaky SiO 2 −Si underlayer, acting like an MOS capacitor. 66 An alternative argument would be to postulate the formation of an opposing negative voltage due to the accumulation of excess negative charges on the surface of the dielectric, only under positive potentials, in agreement with the findings and claims of numerous workers in this field to account for the decrease in the measured contact angle variations and/or surface tension at the liquid interface. To incorporate the development of such polarity-dependent potentials (U*) into our equivalent circuit model and simulate the asymmetric (diode-like) results, we introduce an additional circuit component, a voltage controlled voltage source (VCVS) as outlined in detail below and also in the SI section.…”
Section: ■ Results and Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…If correct, our findings might suggest that a diode could represent either the electrical double layer at the PEG/Teflon interface or the leaky SiO 2 −Si underlayer, acting like an MOS capacitor. 66 An alternative argument would be to postulate the formation of an opposing negative voltage due to the accumulation of excess negative charges on the surface of the dielectric, only under positive potentials, in agreement with the findings and claims of numerous workers in this field to account for the decrease in the measured contact angle variations and/or surface tension at the liquid interface. To incorporate the development of such polarity-dependent potentials (U*) into our equivalent circuit model and simulate the asymmetric (diode-like) results, we introduce an additional circuit component, a voltage controlled voltage source (VCVS) as outlined in detail below and also in the SI section.…”
Section: ■ Results and Discussionsupporting
confidence: 54%
“…The measured C 1s spectra of the system after the breakdown in Figure a and the simulated ones in Figure c are surprisingly but maybe fortuitously similar. If correct, our findings might suggest that a diode could represent either the electrical double layer at the PEG/Teflon interface or the leaky SiO 2 –Si underlayer, acting like an MOS capacitor …”
Section: Resultsmentioning
confidence: 84%
“…If correct, our findings might suggest that a diode could represent either the electrical double layer at the PEG/Teflon interface or the leaky SiO 2 -Si underlayer, acting like an MOS capacitor. 86 Incorporating simulation results yields two important new features, such as the abilities to (i) decouple the electrical properties of the liquid drop from those of the dielectric, and under diverse conditions; (ii) determine a decrease in the conductivity of the liquid after its breakdown, which is contrary to common understanding since strong electrical disturbances are usually expected to cause fragmentation and/or produce additional ionic moieties, hence increasing the conductivity; and (iii) surface a new type of asymmetric behavior of the postbreakdown system with respect to the polarity of the applied potential. This also points to an important question of whether all these obstacles, limiting the performance of electrowetting systems and devices, stem from the very same phenomenon, i.e., charge accumulation.…”
Section: Discovering An Additional Asymmetry In Electrowettingmentioning
confidence: 99%
“…Our results proved that the device exhibits a significant modulation depth change from 3.9% to 5.5% with the effect of gate voltage being due to the increase in the carrier concentration of graphene. According to the theoretical model expression [39] T T τ = ∆ 3.52 / R (3) where τ is the pulse width, ΔT is the SA modulation depth, and T R is the cavity round trip time. Empirical evidence has shown that the pulse width of passively Q-switched lasers has a directly positive relationship with the SA modulation depth.…”
Section: Wwwadvopticalmatdementioning
confidence: 99%
“…Graphene–insulator–semiconductor (GIS) hetero‐junctions have recently received substantial attention due to their long operating lifetime, high efficiency, and outstanding electrical modulation ability. [ 1–3 ] To date, vertical structures based on pristine and nanopatterned graphene films have emerged for electrical applications in high‐performance optical modulator, [ 4 ] electronic storage devices, [ 5 ] and field‐effect tunneling transistors. [ 6 ] As a high mobility 2D material, graphene and its heterostructure can be operated as a widely cross‐band Saturable absorber (SA) for ultrafast laser systems derived from its π–π band structure with dirac point.…”
Section: Introductionmentioning
confidence: 99%